Historical and Architectural Study of the Ambar Shah Mosque, an Ancient Mosque in Dhaka, Bangladesh (American Journal of Interdisciplinary Research and Innovation, 2023)
The development of Islamic cities over the ages has always been aided by magnificent mosques. The religious practices of Islam’s teachings on nationhood serve as an example of this viewpoint, and the mosque concept has gained widespread acceptance as a means of both community building and religious expression. However, this focus on design, function, and aesthetics is examined and addressed as important topics regarding how the Muslim community interacts with mosques. According to this study, the continued performance of Islamic nationhood in the community is seen as indicative of the historic state mosque’s survival as a “iconic colossal edifice.” This study examines the perception of metropolitan city people’ preferences for the continuation of mosques as a symbol of national integration empirically. Because of the significant roles it performed as a location for historical events and as an architectural symbol that represented Islamic laws, this mosque is a structure of extraordinary architectural quality and unexceptional historical importance to the state. Despite the fact that our research was able to capture information on the mosque’s condition and architectural features, it is clear that more information is required to illustrate how to keep the mosque from deteriorating. Future generations must continue to examine every part of the mosque to make sure that the information needed for repair and maintenance work along with the nation’s progress toward modernity and globalization is not lost.